DAMPAK KEBIJAKAN PENANGANAN PANDEMI COVID-19 PADA PEREKONOMIAN DAN KESEHATAN MASYARAKAT DI DESA LEMOH UNER KECAMATAN TOMBARIRI TIMUR KABUPATEN MINAHASA - PANGKEY, INDAH; LENGKONG, FLORENCE; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2021)
This study aims to determine the policy problems of the Covid-19 pandemic that occurred in the community in Lemoh Uner Village, East Tombariri District, Minahasa Regency. This type of qualitative research with a descriptive approach. All data presented and secondary data. Data collection techniques based on observation, interviews and documentation. Data obtained from various sources were analyzed and conclusions were drawn. The problem in this study lies in the impact of the Covid-19 pandemic policy on the economy and public health in Lemoh Uner Village, East Tombariri District, Minahasa Regency. Because of the ongoing Covid-19 pandemic, but now people are getting used to new habits or new normal so they can venture out of the house and do actvities as usual but still adhere to health protocols. Keywords : Impact of Handling Policies, Covid-19 Pandemic, Economy, Health